O complexo geográfico em os sertões de Euclides da Cunha - Farias, Francisca Diana Pereira de (2010)
The relation between geography and literature if has shown sufficiently promising.When considering that as much geography how much literature, constructs representations of the space from its speeches we find initially the point of interaction between both.In this direction, the workmanship "Os Sertões‖ of Euclides of the Wedge in allows them to argue where measured the existing specifications in a literary composition they can directly interest geography in the construction of its representations about the space.However to construct this approach, we take as north the conceptions of the complexity in which we weave the idea of that the workmanship if constitutes a geographic complex.We detach thus, the language of "Os Sertões‖ as one of the aspects that specify the complex in the Euclidean narrative and that it can interest geography in the production of its knowledge.As well as the language, the imagination is understood while an element that in makes possible them to analyze, to understand and to find the direction of the images made use in the space hinterland